Implementasi Pendekatan Balanced Scorecard dalam Evaluasi Kinerja Pelayanan Akademik: Penelitian - Nasir, Moh. (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Optimal academic service is a key pillar in maintaining the quality and competitiveness of study programs in higher education, including Islamic higher education. Students as internal customers play a crucial role in assessing service effectiveness, thus requiring a comprehensive and structured evaluation model. This study aims to analyze student perceptions of academic service performance in the Islamic Education Management Study Program of the Hasan Jufri Islamic Institute of Bawean using the Balanced Scorecard (BSC) approach that encompasses four perspectives: customer, internal business processes, learning and growth, and finance. A descriptive quantitative approach was used with primary data from a Likert-based closed-ended questionnaire to 15 active students, and secondary data from institutional documents. The results show that the customer perspective obtained the highest score, indicating student satisfaction with administrative interactions and services, while the learning and growth perspective received the lowest score, indicating the need for improvements in human resources and academic support systems.